Sensitivity, specificity and accuracy of diagnostic imaging methods for the diagnosis of ectopic ureters in the dog - MANTIS, P.; BROCKMAN, D.; WHATMOUGH, C.; GREGORY, S. P.; LAMB, C. R.; MAHONEY, P.; JAKOVLJEVIC, S. (Journal of the Hellenic Veterinary Medical Society, 2017)
The clinical records of dogs with urinary incontinence, examined at the Queen Mother Hospital for animals between November 1995 and January 2006, were reviewed. Only dogs that had at least one contrast radiographic study, ultrasonographic examination of the ureters and surgical diagnosis were included. All the cases were examined on an individual ureter basis and on a case basis. The sensitivity, specificity and accuracy were calculated for intravenous urography, retrograde urethrography or retrograde vaginourethrography and ultrasonographic examination of the ureterovescicular junctions. Ultrasonographic examination of the ureterovescicular junctions had the higher sensitivity, specificity and accuracy from the imaging methods with only intravenous urography having mildly higher sensitivity when examined on a ureter base. The main failure of ultrasonographic examination of the ureterovescicular junctions was the identification of the correct side of ectopia. When evaluated on a case basis ultrasonographic examination of the ureterovescicular junctions had perfect sensitivity, specificity and accuracy. The lower mainly specificity and accuracy of intravenous urography and retrograde urethrography or retrograde vaginourethrography were probably related to the difficulty in identifying the location of the ureterovesicular junction.